(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Drug rehabilitation is a complex process which can include a diversity of treatment modalities with relative levels of effectiveness. The World Health Organization (WHO) has noted that maximizing the proportion of drug dependent individuals receiving effective addiction treatment would benefit both those individuals as well as society at large. However, the content, features, and delivery of a drug rehabilitation program are important in determining treatment outcomes. Three cases of deaths at rehabilitation centres due to physical violence inflicted by the staff of the centres are reported here. While the society cannot undo tragic events, the responsible institutions can be held to account for their wrongful acts and the family members can be assisted in their pursuit of justice.